An evaluation of microleakage of various glass ionomer based restorative materials in deciduous and permanent teeth: An in vitro study - Teena Singla; I.K. Pandit; Nikhil Srivastava; Neeraj Gugnani; Monika Gupta (Elsevier, 2012)
Aim: To evaluate the microleakage of recently available glass ionomer based restorative materials (GC Fuji IX GP, GC Fuji VII, and Dyract) and compare their microleakage with the previously existing glass ionomer restorative materials (GC Fuji II LC) in primary and permanent teeth. Method: One hundred and fifty (75 + 75) non-carious deciduous and permanent teeth were restored with glass ionomer based restorative materials after making class I cavities. Samples were subjected to thermocycling after storing in distilled water for 24 h. Two coats of nail polish were applied 1 mm short of restorative margins and samples sectioned buccolingually after storing in methylene blue dye for 24 h. Microleakage was assessed using stereomicroscope. Result: Significant differences (P < 0.05) were found when inter group comparisons were done. Except when GC Fuji VII (Group III) was compared with GC Fuji II LC (Group II) and Dyract (Group IV), non-significant differences (P > 0.05) were observed. It was found that there was no statistically significant difference when the means of microleakage of primary teeth were compared with those of permanent teeth. Conclusions: GC Fuji IX GP showed maximum microleakage and GC Fuji VII showed least microleakage. Keywords: Glass ionomer based restorative materials, Microleakage, Stereomicroscope